(untitled) (Research, Society and Development, 2021)
Positive psychology deals with happiness, excellence and optimal human functioning, focusing on positive personality characteristics, well-being and life satisfaction. It characterizes the personality of the individual through the virtues and forces of character that in turn can contribute considerably to happiness in loving relationships. The main objective of this study was to understand the construction of personality from the perspective of positive psychology and how personality attributes are favorable for the construction of well-being and satisfaction in loving relationships. This is a bibliographical research of the narrative, descriptive and exploratory review type with a qualitative approach. The phenomena of optimism, spirituality and creativity contribute to a dynamic understanding of personality and are articulated as protective and promotion factors for a more balanced and satisfactory relationship. According to the research findings, it is possible to affirm that the personality constructs presented by positive psychology called virtues and forces of character are able to contribute considerably to the establishment of well-being and quality in the love relationship.